Risk perception and emergency preparedness against flood affected participants from the primary health care centre, Malaysia: a comparison between genders - Ching, Siew Mooi; Lee, Kai Wei; Maharajan, Mari Kannan; Salim, Hani; Ng, Jun Ying; Ng, Kar Yean; Abdul Rashid, Aneesa; A/P Sivaratnam, Dhashani; Shamsudin, Nurainul Hana; Ahmad, Imran; Ramachandran, Vasudevan (Universiti Putra Malaysia * Fakulti Perubatan dan Sains Kesihatan, 2023)
Introduction: Flooding has become a major natural disaster in Malaysia in recent decades. There may be a gender difference in many aspects related to flood response and practice. This study aimed to examine the gender gap in knowledge, attitudes, and practice of flood preparedness in Malaysia. Method: This cross-sectional study was conducted among patients attending the primary care clinic at Universiti Sains Malaysia health campus, Kelantan. A validated questionnaire was used for data collection. Results: 328 subjects were recruited, 56.1 of them were females. The female respondents were younger than the males (36 vs. 41 years old). However, females have better knowledge, and practice on flood preparedness compared to male respondents. Among those, women were more aware of the local emergency plan than males (p=0.01). More female respondents kept their vaccination and personal medical records in a waterproof container or sealed plastic bag during past and future flood preparations (3-5 day supply of non-perishable food) than male respondents (p<0.05). In addition, with the practice of keeping a one-week supply of medication, and having their medical records in a waterproof container along with a first-aid kit (p=0.001). For future flood preparation, more women would filter the cloudy water through clean clothes for boiling (p=0.035). The determinants of good preparedness for future floods for female were older-age (p=0.001), blue-collar (p=0.043); whereas male were lower household income (p=0.014), being blue collar (0.014) and white collar (0.039) compared with student/retiree based on multivariate logistic regression. Conclusion: Our study reported that the determinants of good preparedness for future floods were older-age, blue-collar and having a lower-household income.